Effect of different high oxygen treatments on preservation of seedless long jujube in low temperature storage. Issue 1 (2nd December 2019) - Xu, Mengjun; Pan, Yanfang; Leng, Juncai; Li, Hui; Li, Xihong
Abstract: The seedless long jujube is perishable and hard to store; so this paper mainly studied the changes of physicochemical and microbial indicators of seedless long jujubes stored at 0 ± 0.5 °C under different high‐oxygen atmospheres. The kernels of freshly harvested jujubes were removed and seedless jujubes were treated with 40, 60, and 100% of O2 (balance N2 ) or 21% of O2 (as control), then stored at 0 ± 0.5 °C and 80–85% relative humidity for 30 days; related indicators were periodically determined. The output of the analyses showed that compared to the control, both 60 and 100% of O2 effectively inhibited the increase of malondialdehyde content and the colony count, maintained microstructure integrity and inhibited the reduction of titratable acid, ascorbic acid content, and volatile components of seedless long jujube. These results demonstrated that high oxygen treatment was a potential solution for extending the shelf life of seedless long jujube. Practical applications: High oxygen treatment is a new technology of preservation for fruits proposed in recent years. It can make up for the shortcomings of low O2 and high CO2 damage in the storage process of fruits by traditional modified atmosphere. In this study, the 60% of O2 and 100% of O2 treatments successfully inhibited the increase of malondialdehyde content and the colony count and maintained titratable acid, ascorbic acid, and structural integrity and delayed the process of the ripeness and senescence of seedless jujube. Thus, high oxygen treatment will be a prospective way to maintain the quality and extend the storage time of seedless long jujube.